2012
DOI: 10.1016/j.fertnstert.2012.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated alteration of oocyte-specific gene expression in polar bodies: potential markers of oocyte competence

Abstract: Objective To confirm that oocyte-specific mRNAs are detectable in the polar body (PB) of MII oocytes and determine the effect of age on oocyte-specific transcript levels. Design Prospective study Setting Hospital-based academic research laboratory Animals CD1 female mice Intervention(s) Aged (40–50 weeks) and young (7–9 weeks) mice were administered pregnant mare's serum gonadotropin (PMSG) and human chorionic gonadotrophin (hCG). Oocytes were fertilized in vitro to assess fertilization and development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 55 publications
1
34
0
Order By: Relevance
“…In addition, different batches of FBS were used during the experiments, and the results remained unchanged (data not shown). In mice, PB degeneration has been associated to oocyte's ageing (Miao et al, 2004) and apoptosis (Jiao et al, 2012). In our conditions, FBS …”
Section: Discussionmentioning
confidence: 69%
“…In addition, different batches of FBS were used during the experiments, and the results remained unchanged (data not shown). In mice, PB degeneration has been associated to oocyte's ageing (Miao et al, 2004) and apoptosis (Jiao et al, 2012). In our conditions, FBS …”
Section: Discussionmentioning
confidence: 69%
“…The depletion of maternal stores of Filia causes a high incidence of aneuploidy that results from abnormal spindle assembly, chromosome misalignment, and SAC inactivation [32]. Our prior work demonstrated that there is a significant decrease in the transcript levels of oocyte-specific genes in aged vs. young PB [12]. Taken together a decline in a large number of different processes, including reduction in chromosome cohesion, alteration in cytoskeletal function and permissive checkpoint control, leading to decline in general fitness of older oocytes, may be contribute to age-related aneuploidy and decline in egg quality [33].…”
Section: Discussionmentioning
confidence: 98%
“…Collection and culture of MII oocytes MII oocytes were collected from young (2-month-old) and aged (12-to 15-month-old) female mice after superovulation as previously described [12]. Oocyte-cumulus cell complexes were recovered from ampullae into Leibovitz L15 medium containing 1 % fetal bovine serum (FBS) 14 h after human chorionic gonadotropin (hCG) administration.…”
Section: Animalsmentioning
confidence: 99%
“…Collectively, these data suggest that impaired mitochondrial output in oocyte is associated with advanced maternal age. Furthermore, oocytes from aged mice exhibited lower expression of oocyte-specific genes (H1foo, Nlrp5, Tcl1, and Zp3) than those derived from their young counterparts (Jiao et al, 2012), suggesting that there is a lower capacity of aged oocytes to produce and store proteins necessary for oocyte function in the time between fertilization and embryonic genome activation.…”
Section: Adult Vs Aged Cowsmentioning
confidence: 98%